Modulation of cytokine production by carnitine - Nicola M. Kouttab; Claudio De Simone (Mediators of Inflammation)
The ability of carnitine congeners to modulate cytokine production by human peripheral blood mononuclear cells (PBMC) was investigated. Modulation of cytokine production by PBMC of young (30 years of age or younger) and old (70 years of age or older) normal donors was first compared. The PBMC were collected over Ficoll–Hypaque and incubated in the presence of various concentrations of acetyl L-carnitine for 24 h. Subsequently the supernatants were collected and examined for cytokine production. The presence of cytokines in tissue culture supernatants was examined by ELISA. The cytokines measured included IL-1α, IL-1β, IL-2, IL-4, IL-6, TNFα, GM–CSF, and IFNγ. The results showed that at 50 μg/ml of acetyl L-carnitine the most significant response was obtained for TNFα. In this regard four of five young donors responded, but only one of five old donors responded. More recently these studies were expanded to examine the ability of L-carnitine to modulate cytokine production at higher doses, 200 and 400 μg/ml, in young donors. The results of these studies showed that in addition to TNFα, significant production of IL-1β and IL-6 was observed. These preliminary studies provide evidence that carnitine may modulate immune functions through the production of selected cytokines.